Experience a fashion branch website. - Lu, Liwen. (2008)
Fashion brand website has been an instrumental and powerful medium because it has a significant impact on long-term profits in brand equity enhancement. As part of the user-centered approach toward website development, this paper takes the online brand experience perspective focusing on usability, content and visual appearance - three determinants of Web interface design. Based on previous research, the author employed eight dimensions and 35 tools of the interactivity concept related to fashion brand websites and examined their current status with two approaches.